STUDENTS' PSYCHOLOGICAL STABILITY AND CHARACTERISTICS OF FORMING STRESS RESILIENCE IN THE ERA OF GLOBALIZATION. (Universal International Scientific Journal, 2026)
: This article analyzes the psychological impact of the globalization process on the student's personality and highlights the methods of forming psychological stability in a modern educational environment. It is argued that the sharp increase in the flow of information, the intensification of the competitive environment, and the processes of social adaptation can cause stress, anxiety, and emotional instability in students. The author recommends reflection, development of emotional intelligence, motivational support, training sessions, and psychoprophylactic approaches as effective tools. The results of the study serve to strengthen a stable mental state in students and ensure their socio-psychological adaptation.
Keywords: : globalization, psychological stability, student personality, stress, emotional intelligence, social adaptation, motivation, psychoprophylaxis